MiR‐375 and miR‐200c as predictive biomarkers of islet isolation and transplantation in total pancreatectomy with islet autotransplantation. (19th August 2016) - Yoshimatsu, Gumpei; Takita, Morihito; Kanak, Mazhar A.; Haque, Waqas Z.; Chang, Charles; Saravanan, Prathab Balaji; Lawrence, Michael C.; Levy, Marlon F.; Naziruddin, Bashoo
Abstract: Background: Total pancreatectomy with islet autotransplantation (TPIAT) is a promising treatment for refractory chronic pancreatitis. Predictable biomarkers for the endocrine function after transplantation would be helpful in selecting patients for TPIAT. This study aims to identify novel biomarkers for predicting the outcome of islet isolation and transplantation in TPIAT patients. Methods: This paper studied microRNA of 31 TPIAT patients and 11 deceased donors from plasma samples before TPIAT. MiR‐7, miR‐200a, miR‐200c, miR‐320, and miR‐375 were analyzed along with patient characteristics and the outcomes of islet isolation and transplantation via univariate and multivariate regression analysis. Results: MiR‐375 before TPIAT showed a significant correlation with ∆C‐peptide ( r = −0.396, P = 0.03) and post‐digestion islet count ( r = −0.372, P = 0.04). And also miR‐200c was significantly correlated with insulin requirement, C‐peptide, and SUITO index at 1 year after transplantation. Moreover it was confirmed that miR‐200c was a predictable factor of endocrine outcome in multi regression analysis ( coefficient = −7.081, P = 0.001). Conclusions: We concluded that miR‐375 and miR‐200c could potentially serve as novel biomarkers in predicting the islet yield in islet isolation and the metabolic function after transplantation for chronic pancreatitis patients. Abstract : Highlight Yoshimatsu and colleagues analyzed microRNAs in total pancreatectomy with islet autotransplantation to predict graft function using preoperative blood samples. MiR‐375 was linked to isolated islet mass, and miR‐200c was correlated with transplant outcome including insulin requirement. They conclude that microRNAs are potentially useful biomarkers for islet transplantation in chronic pancreatitis.